‘Ayo Kuliah’ movement for members of ‘Program Keluarga Harapan’ to college - Hajron, Kun Hisnan; Issholikhah, Lailatun Nissa; Aziz, Maulana Choirul; Hikmah, Ratna Husna Ulil; Khasanah, Farida Uswatun; Nasser, Fathan Abdul (Community Empowerment, 2021)
During the last 8 years (2012-2019), 166 children of â€œProgram Keluarga Harapanâ€ (PKH) in Magelang Regency continued their education to the tertiary level. The highest figures were shown in 2017 and 2018 with 47 children, while the lowest figures were in 2019 with 4 children. The â€˜Program Keluarga Harapanâ€™ (PKH) needs to be supported by innovative and sustainable efforts to break the poverty chain through education. The â€œAyo Kuliahâ€ Movement aims to break the chain of poverty when Children of PKH graduate from college. This service activity is carried out in the form of socialization, mentoring, training, consultation, tutoring, and practice questions (try out). Try out is done before and after the activity which is a form of evaluation of this activity. The results of the try out showed a significant increase from the average pre-test result of 55.71 and post-test of 89.14. This shows that the â€œAyo Kuliahâ€ Movement activities are very effective in increasing the interest of PKH children to continue their studies to college.